Para-Bombay blood group: Report of a rare blood group - Kimberly Fe Joibi; Noor Haslina Mohd. Noor; Mohd Nazri Hassan; Salfarina Iberahim; Wan Suriana Wan Abdul Rahman; Shafini Mohd Yusoff; Marini Ramli; Rosnah Bahar; Nurul Asyikin Nizam Akbar; Zefarina Zulkafli (Asian Journal of Transfusion Science)
Para-Bombay blood group is a rare blood group typically characterized by the absence of H antigens on red blood cell and the presence of ABH substances on secretion. It can be easily missed and often mistaken as blood group O without extended testing. Detection is important as it significantly affect transfusion management. We report two cases of Para-Bombay A blood group in a teaching hospital in a North-Eastern state of Malaysia.